Cytokines unveiled: their impact on oral and multisystem features of lupus erythematosus - Elemam, Noha M.; Talaat, Iman M.; El Meligy, Omar A. (Frontiers in Immunology, 2025)
Systemic Lupus Erythematosus (SLE) is a multifaceted autoimmune disorder characterized by widespread inflammation and immune dysregulation, impacting various organ systems and generating autoantibodies. Oral lesions are a common and distressing manifestation of SLE, significantly affecting patients’ quality of life. Cytokines, key mediators of immune responses, play a crucial role in the pathogenesis of both systemic and oral manifestations of SLE. This review sheds the light on current research on the involvement of various cytokines, including interleukins different interferon types, and growth factors in SLE. The intricate interplay between pro-inflammatory and anti-inflammatory cytokines contributes to the disease’s initiation, progression, and diverse clinical presentations. Elevated levels of pro-inflammatory cytokines exacerbate inflammation, promote apoptosis, and drive autoantibody production. Understanding the specific roles of these cytokines offers potential therapeutic targets for managing SLE and improving patient outcomes.